DEFINING AN OPTIMAL EV CHARGING SERVICE RADIUS: A USER-BASED APPROACH FOR URBAN PLANNING IN PEKANBARU CITY - Putra, Ardiansyah; Yunus, Wan Muhammad; Umar, Zulkarnain (PT. Jurnal Center Indonesia Publisher, 2026)
The growing emphasis on sustainable urban mobility has positioned electric vehicles (EVs) as a strategic component of transport transformation, particularly in developing cities with constrained infrastructure systems. One of the key challenges in supporting EV adoption is the provision of accessible charging infrastructure, which is closely related to user perception of acceptable service distance. This study aims to determine the optimal service distance of Electric Vehicle Charging Stations (EVCS) based on user preferences in Pekanbaru City, Indonesia, and to explore its implications for spatial planning. A quantitative approach was employed using a questionnaire survey of 51 respondents distributed across 15 administrative districts. All respondents were non-EV users, representing potential adopters in the early stage of transition. The survey captured preferred EVCS distance using interval-based categories, along with respondents’ awareness and intention toward EV adoption. The results indicate that the dominant preferred distance falls within the 2–4 km range, with an estimated mean of 3.08 km and a standard deviation of 1.98 km, resulting in an effective range of approximately 1–5 km. Considering urban road network constraints and detour factors, this range is further adjusted to 3–6 km to reflect more realistic travel conditions. These findings suggest that a relatively dense and accessible charging network is required to reduce range anxiety and support EV adoption. From a spatial planning perspective, a 4 km service threshold is proposed as a practical reference for EVCS deployment, representing the central tendency of user preferences within the adjusted range. This study highlights the importance of integrating user-based spatial parameters into infrastructure planning and contributes to the literature by emphasizing the role of perceived accessibility in shaping EV infrastructure demand in developing urban contexts.